18=-3(3z)

Simple and best practice solution for 18=-3(3z) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18=-3(3z) equation:


Simplifying
18 = -3(3z)

Remove parenthesis around (3z)
18 = -3 * 3z

Multiply -3 * 3
18 = -9z

Solving
18 = -9z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '9z' to each side of the equation.
18 + 9z = -9z + 9z

Combine like terms: -9z + 9z = 0
18 + 9z = 0

Add '-18' to each side of the equation.
18 + -18 + 9z = 0 + -18

Combine like terms: 18 + -18 = 0
0 + 9z = 0 + -18
9z = 0 + -18

Combine like terms: 0 + -18 = -18
9z = -18

Divide each side by '9'.
z = -2

Simplifying
z = -2

See similar equations:

| (6p+x+2)+(3p-3x-5)= | | 5y-60+5y-60+3x+45=180 | | 19+5p+6p-14=14p+15-3p-10 | | 15x+22y=40 | | 18-8=x/3 | | 7x^(2/3)-13x^(1/3)-2=0 | | 6-18=-4z | | -6(4x-5)+5(5x-3)-6=2-4 | | -3(4x+2)= | | 86-76=39y-44y | | 4w^2+4w+1= | | -4.22-0.807= | | 3x^(1/2)-7x^(1/4)=6 | | -4*10= | | 32x+24y=640 | | 20n+12=16n-16 | | 8x-7=8(x+2) | | 10y-120+3x+45=180 | | 9/5(-10)+32=f | | X+14/13=12/13x | | x+3/12=5/6 | | 9x-(4x-9)=7+4x | | (2x-7)=7 | | 6-8y=5y+19 | | 3t+6t=16-8+28 | | 8(11v)= | | 3^3/2-6=75 | | 40x^2-83x+42=0 | | -25=m-8 | | 3*2-1/5*4+23 | | 2b-5-11b-7= | | 3t+6t=18-8+28 |

Equations solver categories